Uzaktan Eğitim ve Yabancı Dil Öğrenme Özerkliği1 - Karasu, G.; Sarı, E-Y. E. (2019)
Distance learning and learner autonomy in foreign language learning Although the concept of distance learning has a history of about 200 years, its systematic implementation in education goes in accordance with technological development. In contrast to distance learning, conventional direct teaching has its own limitations, such as the need for time and place. The change in the form of communication and the easiness of conversation in digital environments make it therefore necessary for scientists to show growing interest in distance learning over time. Since technological progress leads to the drastic change of the education, and the removal of local and time limitations in face-to-face education through the positive contribution of new technologies. This fact provides a more individual and self-managed learning opportunity for language learners. Several definitions of the term "distance learning" were created on the basis of various theories. Distance learning is a form of education which continuously develops itself in accordance with the possibilities of technology. Some countries have recognized the need for distance learning and have been working intensively on this issue. As a result of these efforts, distance learning has become both a companion of traditional education and its opponent. In the 2000s, when the phenomenon of individualization increased day by day and the possibilities for independent learning or autonomous learning became much easier, an integrated transformation of technology in education became compulsory. Such multivariate processes, which merge into each other, also change the traditional duties and responsibilities of students and teachers in education. In order to enable language learners to organize and efficiently benefit from their learning environments, learning inside and outside the classroom should be established based on basic didactic and methodological principles. The aim of this article is to emphasize the concept of distance learning in general, to examine the emergence of the concept of learner autonomy in distance learning in the context of basic theories, and to discuss language learning autonomy in this context. Keywords: Distance learning, foreign language teaching, autonomous learning, theories of distance learning, language learning autonomy, learner autonomy in foreign language learning